A novel method for generating p-type wide- and ultrawide-bandgap III-nitride by doping with magnetic elements. (24th August 2021) - Masago, Akira; Shinya, Hikari; Fukushima, Tetsuya; Sato, Kazunori; Katayama-Yoshida, Hiroshi
Abstract: We propose a novel method to generate p-type conduction and low resistivity in wide- and ultrawide-bandgap III-nitride semiconductors via doping of a magnetic element. This method is based on the energetic competition between the covalency of the magnetic element and the ligand nitrogen atoms and the exchange-correlation energy of the magnetic impurity. Using magnetic elements with large exchange-correlation energy, we can obtain p-type wide- and ultrawide-bandgap semiconductors, which are basically difficult to synthesize due to the unipolarity.